ADVANCES IN DENTAL PROSTHETICS: THE ROLE OF CAD/CAM TECHNOLOGY IN DENTURE FABRICATION - Cosmin Bida; Dragos Ioan Virvescu; Dan Nicolae Bosinceanu; Ionut Luchian; Dragos Fratila; Octavian Tunaru; Bogdan Bulancea; Oana Cristina Cretu; Zenovia Surlari; Dana Gabriela Budala (Romanian Journal of Medical and Dental Education, 2024)
The advent of computer-aided design/computer-aided manufacturing (cad/cam) technology represents a paradigm shift in the field of dental prosthetics, particularly in the fabrication of dentures. this paper explores the evolution, current applications, benefits, challenges, and future directions of CAD/CAM technology in denture fabrication. traditional methods of creating dentures, while effective, come with limitations in terms of precision, customization, and time efficiency. CAD/CAM technology addresses these issues by enabling the production of dentures with unparalleled accuracy and fit, using a wide range of biocompatible materials, and significantly reducing the manufacturing time. This review highlights the significant improvements in patient satisfaction and clinical outcomes associated with cad/cam-fabricated dentures. However, the adoption of this technology is not without challenges, including the high costs of equipment and materials, the steep learning curve for dental professionals, and certain material limitations. despite these challenges, the future of CAD/CAM in denture fabrication is promising, with ongoing advancements in technology and materials, increased accessibility through education and training, and the potential for integration with other digital dental technologies. The paper concludes that CAD/CAM technology is poised to continue its transformative impact on denture fabrication, promising improved patient care and efficiency in dental practice.